A diphenylamino-substituted quinacridone derivative: red fluorescence based on intramolecular charge-transfer transition. Issue 23 (16th February 2016) - Wang, Chenguang; Wang, Shipan; Chen, Weiping; Zhang, Zuolun; Zhang, Hongyu; Wang, Yue
Abstract : A red emissive quinacridone derivative has been prepared through construction of an ICT system. This resulted in the first efficient and bright red OLED based on a quinacridone derivative. Abstract : Quinacridone (QA) derivatives are long-established emitting materials for use in organic light-emitting diodes (OLEDs). However, their role in OLEDs has generally been limited to green/yellow-green emitters. Herein, we report a QA-based red emissive OLED material, NPh2 -QA, constructed through the introduction of two strongly electron-donating diphenylamino groups onto the QA core of green emissive N, N ′-dioctyl-substituted QA. The green-to-red change is due to an alteration of the electronic transition responsible for the population of the S1 state, i.e. from a QA-centered π → π* transition to an intramolecular charge-transfer transition. NPh2 -QA can be easily synthesized and it exhibits efficient red emission, with a fluorescence quantum yield of 0.56 in toluene, as well as good thermal stability, with a decomposition temperature of 444 °C. By adopting NPh2 -QA as a dopant emitter, for the first time, an efficient and bright QA-based red OLED has been realized.